A New Frequency for Offshore Wind-farm Based on Component Loss Calculation - Koganti Srilakshmi; P. Aravindhababu; P. Ravi Babu (International Journal of Applied Power Engineering (IJAPE), 2018)
Offshore wind power plants are gaining importance in recent years, as there is adequate space available for its installation, high wind speed, no restriction on the size of turbine blades (no transportation and construction problem) and blades can be allowed to rotate at higher speed without any noise constraint, thereby increasing the rated power. However, the existing offshore wind farms face greater cost related challenges than those of onshore plants. The integration of offshore wind farm with onshore power grid is a complex issue. Feasible solutions for power transmission through cables from offshore wind farms to onshore are HVAC, line commutated HVDC  and  VSC-HVDC.  This paper analyses the various schemes for integration of offshore wind farm with onshore power grid and suggests that LFAC with submarine cable operating at 0.7 Hz is an optimal choice in obtaining better performances.